Health promotion in Family Health Strategy: the perception of the nursing staff Crato - CE - Danielle Lopes de Alencar; Anna Laryssa Ribeiro de Oliveira Brito; Kenya Waléria de Siqueira Coelho Lisboa (Universidade de Fortaleza, 2012)
Objective: To evaluate the perception of the nursing staff of the Family Health Strategy (FHS) on health promotion. Methods: This was a qualitative and descriptive study, which occurred in nine FHS of the city of Crato-CE in the period October-December 2010. The subjects were nine nurses and eight of the nursing technicians with service time of three to eight years at FHS investigated. Randomly chosen and electing the criterion of saturation data, we used semi-structured interview, which was recorded. During data analysis, we opted for collective subject discourse (CSD), which emerged the central ideas that enabled the formation of CSD for each professional category. The subjects were informed about the research objectives by submitting the Term of Consent, which was signed by all. The project was approved by the Ethics Committee at the Rural University of Cariri (RUCA), with approval No. 21/2010. Results: It was observed that the conceptual and practical vision on health promotion approaches the concept of prevention, however, nurses recognize health more broadly, in the context of the social construction of individual, differing from the CSD of the nursing technicians. The actions taken in the field of health promotion are still delimited by lectures. Conclusion: Perceptions of professionals are constituted by a weakness related to CSD and the actions performed by them, constituting an obstacle to the consolidation of a new model of care that has as central to health promotion.